2021
DOI: 10.21203/rs.3.rs-654012/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidative Stress and Motion Sickness during Offshore Sailing

Abstract: Purpose: Offshore Ocean Sailing is a highly demanding activity in which subjects are exposed to psychophysical stressors for a long time. To better define the physiological adaptations, we investigated the stress response of subjects exposed to 3-days long ocean navigation with disruption of circadian rhythms.Methods: 6 male subjects were involved in the study and provided urine and saliva samples before setting sail, during a single day of inshore sailing, during 3-days long ocean navigation, and at the arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Past studies have investigated the impacts of sailing bouts on neuromuscular functions, energy demands and stress hormones. These studies have reported increases in neuromuscular fatigue 4 , muscular damage 8 , cognitive impairment 9 , motion sickness 10 and elevated cortisol levels after sailing bouts 11 . Although the current literature suggests that significant fatigue is induced by offshore sailing, little evidence is available in a crewed context.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have investigated the impacts of sailing bouts on neuromuscular functions, energy demands and stress hormones. These studies have reported increases in neuromuscular fatigue 4 , muscular damage 8 , cognitive impairment 9 , motion sickness 10 and elevated cortisol levels after sailing bouts 11 . Although the current literature suggests that significant fatigue is induced by offshore sailing, little evidence is available in a crewed context.…”
Section: Introductionmentioning
confidence: 99%